Survival after Locoregional Treatments for Hepatocellular Carcinoma: A Cohort Study in Real-World Patients. (3rd May 2012) - Signoriello, Simona; Annunziata, Annalisa; Lama, Nicola; Signoriello, Giuseppe; Chiodini, Paolo; De Sio, Ilario; Daniele, Bruno; Di Costanzo, Giovanni G.; Calise, Fulvio; Olivieri, Graziano; Castaldo, Vincenzo; Lanzetta, Rosario; et al.
Abstract : Evidence of relative effectiveness of local treatments for hepatocellular carcinoma (HCC) is scanty. We investigated, in a retrospective cohort study, whether surgical resection, radiofrequency ablation (RFA), percutaneous ethanol injection (PEI), and transarterial embolization with (TACE) or without (TAE) chemotherapy resulted in different survival in clinical practice. All patients first diagnosed with HCC and treated with any locoregional therapy from 1998 to 2002 in twelve Italian hospitals were eligible. Overall survival (OS) was the unique endpoint. Three main comparisons were planned: RFA versus PEI, surgical resection versus RFA/PEI (combined), TACE/TAE versus RFA/PEI (combined). Propensity score method was used to minimize bias related to non random treatment assignment. Overall 425 subjects were analyzed, with 385 (91%) deaths after a median followup of 7.7 years. OS did not significantly differ between RFA and PEI (HR 1.11, 95% CI 0.79–1.57), between surgery and RFA/PEI (HR 0.95, 95% CI 0.64–1.41) and between TACE/TAE and RFA/PEI (HR 0.88, 95% CI 0.66–1.17). 5-year OS probabilities were 0.14 for RFA, 0.18 for PEI, 0.27 for surgery, and 0.15 for TACE/TAE. No locoregional treatment for HCC was found to be more effective than the comparator. Adequately powered randomized clinical trials are still needed to definitely assess relative effectiveness of locoregional HCC treatment.